Faktor Yang Mempengaruhi Cash Holding Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Stefany, Agustine Ekadjaja (Jurnal Paradigma Akuntansi, 2019)
The purpose of this study is to obtain empirical evidence on the effect of cash flow, net working capital, and growth opportunities to cash holding that listed in Indonesia Stock Exchange, with a total of 248 samples. This study uses secondary data which were tested using panel data regression analysis with Eviews. The result of this study suggests that cash flow, net working capital, and growth opportunity have no effect to cash holding